2019
DOI: 10.1016/j.ebiom.2019.02.051
|View full text |Cite
|
Sign up to set email alerts
|

OVA66 promotes tumour angiogenesis and progression through enhancing autocrine VEGF-VEGFR2 signalling

Abstract: Background Activation of autocrine VEGF-VEGFR2 signalling in tumour cells activates cell proliferation, survival, and angiogenesis, all of which are crucial for tumour progression. Ovarian cancer-associated antigen 66 (OVA66) is now known to be overexpressed in multiple tumours and plays a role in tumour development, but the underlying mechanisms has not been fully investigated. Methods We employed ovarian and cervical cancer cells and mouse models to detect the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…Accordingly, in our study, we also found that silencing VEGF in NPC cells led to a decrease in N-cadherin, vimentin and MMPs and increase in E-cadherin, suggesting that VEGF can affect metastasis via EMT and MMPs in NPC cells. Emerging findings have demonstrated that autocrine VEGF-VEGFR2 signalling serves as an angiogenic modulator that controls tumorigenesis and malignant behaviour in many cancer cells, including ovarian cancer and skin epithelial cancer [11,[16][17][18]21]. In our study, we found that NPC cells secreted VEGF and promoted angiogenesis in a paracrine manner, further supporting the role of VEGF in tumour progression.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Accordingly, in our study, we also found that silencing VEGF in NPC cells led to a decrease in N-cadherin, vimentin and MMPs and increase in E-cadherin, suggesting that VEGF can affect metastasis via EMT and MMPs in NPC cells. Emerging findings have demonstrated that autocrine VEGF-VEGFR2 signalling serves as an angiogenic modulator that controls tumorigenesis and malignant behaviour in many cancer cells, including ovarian cancer and skin epithelial cancer [11,[16][17][18]21]. In our study, we found that NPC cells secreted VEGF and promoted angiogenesis in a paracrine manner, further supporting the role of VEGF in tumour progression.…”
Section: Discussionsupporting
confidence: 80%
“…Emerging findings have demonstrated that autocrine VEGF-VEGFR2 signalling serves as an angiogenic modulator that controls tumorigenesis and malignant behaviour in many cancer cells, including ovarian cancer and skin epithelial cancer 11 , 16 - 18 , 21 . In our study, we found that NPC cells secreted VEGF and promoted angiogenesis in a paracrine manner, further supporting the role of VEGF in tumour progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cancer, angiogenesis involves interaction between tumor cells, endothelial cells, and mesenchymal cells, which is orchestrated by growth factors or cytokines and their corresponding receptors. Among them, VEGFA plays a key role in the process of angiogenesis . Recent studies have shown that a variety of cancer cells can upregulate the expression of VEGFA, thereby promoting tumor‐induced angiogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it is reported that NudCD1 promotes proliferation, migration, and invasion of renal carcinoma cells [11]. Additionally, NudCD1 promotes tumor angiogenesis and progression through enhancing autocrine VEGF-VEGFR2 signaling [12]. NudCD1 affects the progression of renal cell carcinoma through regulating the LIS1/dynein signaling pathway [13].…”
Section: Introductionmentioning
confidence: 99%